Deskripsi Hasil Belajar Peserta Didik Pada Materi Yang Menerapkan Perhitungan Kimia Dengan Menggunakan Modul Berbasis Guided Inquiry - Ruci Aditya Rushiana; Iryani Iryani (Universitas Negeri Padang, 2021)
This study aims to describe the learning outcomes of students on materials of chemical calculations using guided inquiry-based modules. The materials for chemical calculations include chemical equilibrium, salt hydrolysis, and buffer solutions. The type of this research is literature research with a semi-systematic approach. The data source is in the form of secondary data from reputable and non-reputable scientific journals. The data were collected using the documentation method and analysed using content analysis techniques. Based on the results of the journal review that has been done, it can be concluded that the learning outcomes of students in learning using guided inquiry-based modules have increased significantly in materials of chemical calculations, namely chemical equilibrium and salt hydrolysis and buffer solutions. The use of guided inquiry-based modules can encourage students to be active during the learning process and there are models and key questions that can make help students to find concepts and the existence of practice questions at the application stage that can strengthen students understanding.